Analysis of Production Performance and Medicine Cost Expenditure Before and After Avian Infectious Bronchitis in Commercial Broiler Farms - Viqih, Muhammad; Gunistiyo, Gunistiyo; Raharjo, Hartanto Mulyo (Universitas Airlangga, 2023)
Avian infectious bronchitis is one of the diseases that can lead to losses in broiler farming. To investigate its impact, we conducted a recapitulation of plasma maintenance (RHPP) results data gathered from 5 clusters that tested positive for avian infectious bronchitis using PCR and ELISA tests. Subsequently, the RHPP data underwent quantitative analysis using paired sample t-test method. The results of this analysis revealed significant differences in the variables of performance index (PI), feed conversion ratio (FCR), and medicine costs within several clusters before and after being infected with avian infectious bronchitis. This study was important for the future to address zero hunger issues.